A Defense Mechanism of the Characters in Stephen King’s Book “Bazaar of Bad Dreams” - Pakaya, Sitti Safirah Mardhatillah; Podungge, Rusni; Muhamad, Farid (Universitas Negeri Gorontalo, 2025)
This study aims to describe the use of ego defense mechanisms by characters in three short stories by Stephen King in the book “Bazaar of Bad Dreams”, namely Premium Harmony, A Death, and Bad Little Kid, using Sigmund Freud’s psychoanalytic theory that focuses on ego defense mechanisms. The study uses a qualitative descriptive method with a psychoanalytic approach. Data were collected through short story selection, reading and recording, and coding, then were analyzed through data classification, data analysis, description of analysis results, conclusions of analysis results, and reporting of research results. The results show that the characters in the three short stories display various ego defense mechanisms in dealing with conflict and stress, including denial, reaction formation, projection, displacement, rationalization, and repression. The analysis reveals the complex psychological dynamics of each character and how internal and external factors influence their ego defense mechanisms. It also compares their applications in the context of Indonesian society. Ego dominance is seen in the character’s attempts to balance id drives, superego demands, and reality through different ego defense mechanisms.